2018
DOI: 10.1002/elan.201800218
|View full text |Cite
|
Sign up to set email alerts
|

The Signal Amplification in Electrochemical Detection of Chloramphenicol Using Sulfonated Polyaniline‐chitosan Composite as Redox Capacitor

Abstract: In this work, a novel redox capacitor was designed for signal amplification in electrochemical detection. It was fabricated by co‐electrodeposition of a conducting polymer, sulfonated polyaniline (SPAN) and chitosan on a glass carbon electrode, and its function was evaluated for being a localized source to transfer electron between FcCOOH (Fc) and Ru(NH3)6Cl3 in solution via redox cycling. Furthermore, the electrochemical detection of chloramphenicol, a broad‐spectrum antibiotic was performed using the redox c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…This result demonstrated that SPANÀ CS composite could be sequentially charged and discharged steady in each cycle when Ru(II/III) and catechol/o-benzoquinone were presented. This experimental result was consistent with our previous work [40] and the Payne group's work [44,45]. It also ensured the stability of amplified signal required in this experiment.…”
Section: Study Of Enzyme Reaction Coupling With Ecc Redox Cyclesupporting
confidence: 92%
See 4 more Smart Citations
“…This result demonstrated that SPANÀ CS composite could be sequentially charged and discharged steady in each cycle when Ru(II/III) and catechol/o-benzoquinone were presented. This experimental result was consistent with our previous work [40] and the Payne group's work [44,45]. It also ensured the stability of amplified signal required in this experiment.…”
Section: Study Of Enzyme Reaction Coupling With Ecc Redox Cyclesupporting
confidence: 92%
“…The synthetic experiment followed the previous work [40]: Aniline of 0.09 g and 3-Aminobenzenesulfonic acid of 0.24 g were added in 20.0 mL 0.15 mol L À 1 HCl, then the initiator of 10.0 mL 0.06 mol L À 1 ammonium persulfate was placed into the above solution. The whole copolymerization reaction was continuously carried out for 24 hours at 5°C under static conditions.…”
Section: Preparation Of Sulfonated Polyaniline (Span)mentioning
confidence: 99%
See 3 more Smart Citations